Membership matters: Coerced recruits and rebel allegiance. (September 2017) - Gates, Scott
Unable to attract enough voluntary recruits, many rebel groups rely on force to fill their ranks. Given that the group used force to compel individuals to join, a coerced conscript would be presumed unlikely to be loyal and would be expected to desert at the first opportunity. Yet, groups that have relied on coerced recruitment retain their members just as well as, if not better than, rebel armies that rely on voluntary methods of recruitment. This is a puzzle. How do rebel groups maintain allegiance and prevent desertion, especially if they rely on abduction to staff their ranks? A recruit can be forced to join a rebel group, but continuing to rely on coercion to enforce retention is too costly and not sustainable. These groups must find a way to reduce the costs of retention. The solution to this puzzle rests in the mechanisms of socialization that shape the allegiance of forcibly recruited soldiers. Socialization mechanisms are traced through three outcomes: compliance (or Type 0 socialization), role learning (Type I socialization), and norm internalization (Type II socialization). Integrating socialization theory and a rational choice analysis demonstrates that mechanisms that alter preferences through Type II socialization are effective in retaining recruits; the highest level of retention occurs when several mechanisms work in concert. Illustrative case studies of the Lord's Resistance Army from Uganda, the Revolutionary United Front in Sierra Leone, the Maoists in Nepal, and the Liberians United for Reconciliation and Democracy (LURD) show that a reliance on child soldiers, group assets (pecuniary and non-pecuniary), organizational structure, and the nature of military contestation shape when different mechanisms are effective or not.